Herniated disc of lumbar spine caused by bone cement leakage after kyphoplasty – A case report and literature review. (November 2021) - Tzeng, Shih-Wei; Chen, Ching-Lin
Abstract: Introduction and importance: To describe an unusual case with herniated disc caused by bone cement leaking to disc space after kyphoplasty. Case presentation: We reported a 72-year-old woman with L4 osteoporotic compression fracture. New-onset of left sciatica, numbness and intermittent claudication suffered her immediate after kyphoplasty. Herniated disc caused by bone cement leaking to disc space after kyphoplasty. The patient was post decompressive operation of L34 and the symptoms subsided well then. Clinical discussion: Percutaneous vertebroplasty (PVP) was a common procedure today. Especially to back pain caused by osteoporotic fracture, reported pain relief rate was satisfactory. Current studies about bone cement leakage showed kyphoplasty less than vertebroplasty. However, for the mechanism and stress effect of balloon expansion, new weak points and cracks over endplate was created, which may cause bone cement leakage to disc space and related symptoms. Conclusion: Kyphoplasty was a common, effective and minimal invasive operation for patients with compression fracture of spine. Cement leakage to intervertebral disc space was generally asymptomatic, but it should be avoided as much as possible. The leakage could affect the stability and weight-bearing of spinal column. Accelerated degenerative process of disc would be found and newly herniated disc would be noted. It should be ceased the procedure when relative amount of bone cement leakage to disc space during kyphoplasty. Highlights: Kyphoplasty as a common, effective procedure for compression fracture Bone cement leakage in kyphoplasty less than vertebroplasty Bone cement leakage affect spine stability Herniated disc from bone cement leaking to disc space might cause annoying symptoms